Pelatihan Internalisasi Nilai Aswaja Berbasis Storytelling Digital pada Forum Makesta Ipnu dan Ippnu di Kampus Iiknu - Rr. Kusuma Dwi Nur Ma’rifati; Sani Latifatul Khilmina; Lilatul Izati; Imam Supriyadi; Isnawati Nur Afifah Latif; Ninik Hidayati (ARDHI : Jurnal Pengabdian Dalam Negri, 2026)
Digital technology has transformed how young people learn, communicate, and access religious information, creating opportunities and challenges for internalizing moderate Islamic values. This community service program aimed to strengthen Ahlussunnah wal Jama’ah (Aswaja) values and improve digital literacy among IPNU and IPPNU cadres through digital storytelling training at the MAKESTA Forum of IIKNU Tuban Campus. The program used an Asset Based Community Development (ABCD) approach through five stages: Define, Discovery, Dream, Design, and Destiny. Participants were purposively selected from MAKESTA participants as novice cadres with potential in organizational experience, communication, creativity, and digital media use. Data were collected through observation, interviews, group discussions, documentation, pre-tests, post-tests, and evaluation of digital storytelling products. Results showed improved understanding of Aswaja values, particularly tawassuth, tasamuh, tawazun, and i’tidal. Participants also improved their abilities to develop messages, construct narratives, produce creative digital content, and communicate moderate Islamic values. The program produced educational videos, social media content, and visual narratives, supporting innovative kaderization and developing creative, adaptive, and responsible digital da’wah agents.